Comparison of inflammation and oxidative stress levels by the severity of obesity in prepubertal children - Ni Luh Putu Surya Candra Eka Pertiwi; I Gusti Lanang Sidiartha (Indonesian Pediatric Society, 2017)
Background Children with severe obesity are more likely to develop diabetes and cardiovascular diseases at a younger age. Inflammation and oxidative stress associated with childhood obesity may be important in the development of insulin resistance and atherosclerosis. Objective To compare levels of high-sensitivity C-reactive protein (hsCRP) and malondialdehyde (MDA) by the severity of obesity in prepubertal children aged 6 to 10 years. Methods We conducted a cross-sectional study at the Pediatric Nutrition and Metabolic Syndrome Clinic, Sanglah Hospital, Bali, from August to December 2015. Subjects were categorized into three body mass index (BMI) groups, according to the 2000 Centers for Disease Control and Prevention growth chart: overweight (85th-94.9th percentile), obese (95th-98.9th percentile), or severely obese (â‰¥ 99th percentile). Plasma MDA and serum hsCRP were analyzed in blood specimens obtained at enrollment. Data were analyzed by Kruskal-Wallis test, followed by Mann-Whitney U test for post-hoc comparison between groups. Results Subjects were 20 overweight children, 29 obese children, and 28 severely obese children. Levels of MDA were significantly higher in the severely obese [median 0.25 (IQR 0.1) Î¼mol/L] than in obese subjects [median 0.19 (IQR 0.1) Î¼mol/L; P=0.001], and than in overweight subjects [median 0.16 (IQR 0.1) Î¼mol/L; P<0.0001]. Also, the severely obese children had significantly higher hsCRP levels compared to obese [median 3.2 (IQR 2.0) mg/L vs. 1.3 (1.6) mg/L, respectively; P<0.0001] and compared to overweight children [median 0.7 (IQR 0.6) mg/L; P<0.0001]. Â Â Â Conclusion Prepubertal children at the â‰¥ 99th percentile for BMI (severely obese) are more likely to have significantly higher hsCRP and MDA compared to those in the obese and overweight groups. Â